2010
DOI: 10.3892/mmr.2010.386
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory role of protease-activated receptor-2 in intestinal ischemia/reperfusion injury in rats

Abstract: Abstract. Protease-activated receptors (Pars) are widely recognized for their modulatory properties during inflammation. The aim of the present study was to examine the role of Par-2 on ischemia/reperfusion-induced small intestinal injury in rats. intestinal damage was induced in male Wistar rats by clamping both the superior mesenteric artery and the celiac trunk for 30 min, followed by reperfusion for 60 min. expression of Par-2 in the intestinal mucosa was estimated by Western blot analysis and real-time Pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Liver Myeloperoxidase Activity Assays Myeloperoxidase (MPO) activity was measured according to the method of Yoshida et al 22) Tissue was homogenized in 50 mM phosphate buffer (pH 6.0) containing 0.5% hexadecyltrimethylammonium bromide. The supernatant remaining after centrifugation was then mixed with 10 mM phosphate buffer (pH 6.0) and 1 mL of 1.5 mM o-dianisidine hydrochloride containing 0.2 mM H 2 O 2 .…”
Section: )mentioning
confidence: 99%
“…Liver Myeloperoxidase Activity Assays Myeloperoxidase (MPO) activity was measured according to the method of Yoshida et al 22) Tissue was homogenized in 50 mM phosphate buffer (pH 6.0) containing 0.5% hexadecyltrimethylammonium bromide. The supernatant remaining after centrifugation was then mixed with 10 mM phosphate buffer (pH 6.0) and 1 mL of 1.5 mM o-dianisidine hydrochloride containing 0.2 mM H 2 O 2 .…”
Section: )mentioning
confidence: 99%
“…A very recent study revealed that PAR-2 participates in small intestinal ischemia-reperfusion by observing the protective effects against reperfusion injury using PAR-2 antibody [31], and other publications have supported that PAR-2 plays an important role in acute lung injury [32,33]; therefore, in present study, we did not choose the agent to inhibit PAR-2 to observe the precise role in lung injury.…”
Section: Discussionmentioning
confidence: 84%
“…6 Indeed, Xa and IIa cleave the protease-activated receptors (PAR) which subsequently induce the production of vascular adhesion, proinflammatory and pro-fibrotic molecules. 7 It was demonstrated that PAR-1 and PAR-2 activated by coagulation proteases, play a crucial role in IRI, 8,9 in association with fibrosis, tissue remodeling and inflammation. 10,11 As a consequence, the coagulation cascade is one major target to limit IRI.…”
mentioning
confidence: 99%